2006
DOI: 10.1210/en.2005-1079
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Steroid Modulation of Stress-Induced Hypothalamo-Pituitary-Adrenal Activity and Anxiety Behavior: Role of Central Oxytocin

Abstract: Intracerebroventricular administration of oxytocin reduces anxiety behavior and hypothalamo-pituitary-adrenal (HPA) responses to stress in female rats. Similar changes are seen in late-pregnant rats, and oxytocin-sensitive pathways may mediate these effects. This study investigated anxiety behavior and stress responses using a gonadal steroid model of late pregnancy, which is known to increase endogenous oxytocin expression. Compared with continuous progesterone treatment, 3-d withdrawal of progesterone after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
3
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 71 publications
1
45
3
1
Order By: Relevance
“…The anti-anxiolytic effect of oxytocin knockout has not been confirmed in males [1,20]. In addition, central oxytocin activity to attenuate anxiety response to a mild stressor might be under the strong regulation of gonadal steroid in mice and rats [17], suggesting a strong relation between oxytocin and gonadal steroids. No inhibition of behavioral response to isolation by oxytocin in this study also may have been due to lower estrogen influence in steers castrated before sexual maturation than that in females.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-anxiolytic effect of oxytocin knockout has not been confirmed in males [1,20]. In addition, central oxytocin activity to attenuate anxiety response to a mild stressor might be under the strong regulation of gonadal steroid in mice and rats [17], suggesting a strong relation between oxytocin and gonadal steroids. No inhibition of behavioral response to isolation by oxytocin in this study also may have been due to lower estrogen influence in steers castrated before sexual maturation than that in females.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the E 2 replacement applied in the present study has been shown to result in equal proestrus-resembling plasma E 2 concentrations in both vehicle- and PRL-treated animals [8]. This is crucial as gonadal steroids were found to influence hypophyseal PRL secretion [51], expression of PRL receptors in the brain [52,53,54], neuronal c- fos stress responses [55] as well as the activity of the OXT system [56,57,58]. However, future experiments are needed to demonstrate if estrogens play a permissive role for the observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…In males, the VMH is critical in the regulation of sexual and aggressive behaviors primarily through the actions of estrogen on ER ␣ [Harding and McGinnis, 2004;Nelson and Trainor, 2007]. OT receptor expression in the VMH is up-regulated following increases in estradiol [Bale et al, 2001] or decreases in progesterone [Windle et al, 2006], and estrogen and oxytocin receptor mRNA is found to be co-expressed in VMH neurons [Devidze et al, 2005]. Taken together with our data, these findings suggest that variation in maternal care across the whole of the postnatal period can induce changes in offspring reproductive strategies.…”
Section: Neurobiological Changes Associated With Weaning Age: Plasticmentioning
confidence: 99%